Pengaruh Independensi, Fee Audit, dan Kompetensi Auditor Terhadap Kualitas Audit (Studi Kasus Pada Kantor Akuntan Publik di Wilayah Kota Bekasi) - Loura Indrawijaya; Maidani Maidani; Cris Kuntadi (Peneliti.net, 2023)
This research reviews independence, audit fee, and auditor competence that effect audit quality. Based on relevant research that has been collected by researchers, this study aims to strengthen the theory and phenomenon of the relationship or influence between variables. The purpose of writing this article is to build a hypothesis on the influence between variables for use in further research. Article literature review has four hypotheses, namely: (1) independence has a effect on audit quality; (2) audit fees has a effect on audit quality; (3) competence has a effect on audit quality.